A theory of communication in distributed software development teams - LEITÃO JUNIOR, Nelson Galvão de Sá (2021)
Effective communication is a significant and lingering challenge in Distributed Software Development teams. With this in mind, researchers have been dedicating time and effort to construct tools and methodologies for supporting a better efficacy of communication in those teams. Still, this effort has not been supported by any scientific theory created to describe the Communication Phenomenon in this context, despite the importance of communication in those teams. Theories are important for researchers as they offer a common conceptual framework for supporting facts and knowledge, and Computer Science researchers have been using theories to support their interventions, findings, hypothesis, and methodological procedures. This study aims to describe the communication phenomenon in Distributed Software Development teams by constructing a communication theory. By achieving this goal, this study also aims at establishing a theoretical base for future studies in academia and a reference for the industry and thereby help mitigate the lingering challenging nature of communication in Distributed Software Development teams. This study is structured in a three-step methodological design, as follows: Step 1 - the Consolidation of the Study Gap, based on an exploratory and non-extensive literature review; Step 2 - the Theory Construction, via Grounded Theory from the ground-up, including an extensive analytical process; Step 3 - the Theory Strengthening, based on a Systematic Mapping Study, a positioning procedure of the emerged theory within the contemporary theoretical landscape, and an evaluation process. Findings include the emerged theory that describes the communication phenomenon in distributed teams, named the Distributed Communication Dimensions Theory. Findings also include the results of the Systematic Mapping Study and considerations on the positioning process. Furthermore, findings include the results from the evaluation of the theory, based on the results of a Focus Group session with Distributed Software Development practitioners, and considerations on three sets of credibility criteria. Our main conclusion is that the Communication Phenomenon in Distributed Software Teams is described by multidisciplinary actions and constructs, represented by seven communication dimensions and 34 theoretical components, including culture, language, time zones, practices, meetings, media, as well as behavioral and social constructs.